Phytochemical composition and therapeutic effects of amaranthus viridis linn: a review - R, Bharathi D; G, Sahana K; C, Mahesh; Babu, Anjali; S, Karthik; M , Rupesh Kumar; B, Ramesh (International Journal of Indigenous Herbs and Drugs, 2022)
The plant Amaranths viridis Linn, an annual herb from the Amaranthaceae family, is used in traditional medicine to cure a range of ailments and to determine the various criteria for pharmacognostical standards. A. vilidis L. leaf extract contains a number of biologically active substances, including saponins, tannins and phenols, flavonoids, alkaloids, cardiac glycosides, steroids, and triterpenoids. The amino acids lysine, arginine, histidine, cysteine, phenylalanine, leucine, isoleucine, valine, threonine, methionine, and tyrosine are among the substances found in A. viridis. A. vilidis L contains a chemical compound with potent anti-inflammatory, antihepatotoxic, antiulcer, antiallergic, and antiviral effects. They also exhibit antimicrobial, antipyretic, antihyperlipidemic,antidiabetic, and anti-HMG-CoA reductase activities.